2009
DOI: 10.1016/j.ejvs.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Interleukin-8 and Monocyte Chemoattractant Protein-1 Expression within the Abdominal Aortic Aneurysm and their Association with Mural Inflammation

Abstract: Pathways involving IL-8 and MCP-1 may be involved in AAA pathogenesis. IL-8 may be directly involved in the chemotaxis of T(H)-lymphocytes into the AAA wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…We also found that inflammatory molecules and macrophage infiltration were increased in the aneurysmal wall. MCP-1 is a major factor promoting the accumulation of macrophages in atherosclerosis 25 and abdominal aortic aneurysms, 26 and it is involved in the patho- We demonstrated that MR activation with DOCA resulted in a high incidence of cerebral aneurysms, and the mRNA levels of oxidative stress and inflammatory genes were increased despite a moderate increase in blood pressure. Oxidative stress and inflammation are associated with RAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that inflammatory molecules and macrophage infiltration were increased in the aneurysmal wall. MCP-1 is a major factor promoting the accumulation of macrophages in atherosclerosis 25 and abdominal aortic aneurysms, 26 and it is involved in the patho- We demonstrated that MR activation with DOCA resulted in a high incidence of cerebral aneurysms, and the mRNA levels of oxidative stress and inflammatory genes were increased despite a moderate increase in blood pressure. Oxidative stress and inflammation are associated with RAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Loss of function of DPPI resulted in a diminished recruitment of neutrophils to the elastase-injured aorta and an impaired production of CXC-chemokine ligand 2. 22 The role of neutrophils in AAA pathogenesis can be further reinforced by the finding that IL-8, a CXC chemokine involved in neutrophil chemotaxis and degranulation, 18 is increased in the plasma 77 and the aortic wall 18,63 of patients with AAA.…”
Section: Polymorphonuclear Leukocytesmentioning
confidence: 93%
“…The protein, consisting of 72 amino acids in its mature form, is identified as a basic and heparin-binding protein [7,9,11,12]. IL-8 also exhibits chemotactic activities against T lymphocytes and basophils, as well as neutrophils in vitro [9,10].…”
Section: Discussionmentioning
confidence: 99%